Materials for a debate on the 15-minute city: Public transportation’s effect on urban space and time in two Asia-based alternative proposals - Davide Maria Bruno; Guido Musante; Fabio Dacarro (Journal of Asian Architecture and Building Engineering)
This work aims to encourage a debate about Carlos Moreno’s “15-minute city” – a recent, popular concept to make contemporary cities more livable by decentralizing the urban environment into self-sufficient, walkable units. After reviewing the principles of Moreno’s idea and its current criticism, this paper illustrates two projects, Woven City (Japan) and Gwangmyeong New Town (Korea), that start from the “15-minute city” intentions; nonetheless, arrive at opposite conclusions. These proposals focus on transport – a central element in Moreno’s model, paradoxically, due to its absence – as the key issue to realizing a sustainable urban environment while preserving the notion of a city as a vast, complex and centralized organism. Both projects rethink public transportation to address the social problem of the time wasted on transferring, a crucial concern of the 15-minute city. Woven aims at minimizing this time through futuristic infrastructures, while Gwangmyeong makes transportation time “usable,” allowing people to carry out activities while transferring. These projects’ results are yet to be tested. Nevertheless, by illustrating these proposals, this study shows how alternative options are possible for the realization of a sustainable modern city.